Natural Human Infections with Plasmodium cynomolgi, P. inui, and 4 other Simian Malaria Parasites, Malaysia - Yap, Nan Jiun; Hossain, Hanisah; Nada-Raja, Thamayanthi; Romano, Ngui; Muslim, Azdayanti; Hoh, Boon-Peng; Khaw, Loke Tim; Kadir, Khamisah Abdul; Divis, Paul Cliff Simon; Vythilingam, Indra; Singh, Balbir; Lim, Yvonne Ai-Lian (Centers for Disease Control and Prevention, 2021)
We detected the simian malaria parasites Plasmodium knowlesi, P. cynomolgi, P. inui, P. coatneyi, P. inui–like, and P. simiovale among forest fringe–living indigenous communities from various locations in Malaysia. Our findings underscore the importance of using molecular tools to identify newly emergent malaria parasites in humans.